Analysis Of Sharia Purple Load System On Settlement Of Sharia In Islamic Law Perspective Indonesia - Fajriawati Fajriawati; Harisman Harisman; Dedi Muhruzani Nurlubis (Proceeding International Seminar of Islamic Studies, 2019)
This study analyzes the normative juridical approach in the process of qualitative data. Sharia pawning loading system is a new economic phenomenon since the regulation of Law 7 of 1992 in conjunction with Law 10 of 1998 in conjunction with Law number 21 on Islamic banking, this regulation is responded by the National Sharia Council and issued Fatwa number 25 / DSN- MUI / III / 2002 concerning rahn. The problem formulation in this research is how the sharia pawning system is charged to the pawn holder and whether the imposition of sharia pawning costs can be said to be usury in the perspective of Islamic Law based on the results of the analysis of the loading system can be seen from insurance services storage costs, security costs and processing fees. Therefore, Islamic pawnshop is very necessary for the future to tie the economy in Indonesia.